The Influence of Family Control and Gender Diversity on Financial Performance: Leverage and Tangibility as Mediating Role - Anita, Rizqa; Suseno, Giri; Abdillah, Muhammad Rasyid; Andira, Aulia Rona (Jurnal Akuntansi dan Bisnis, 2023)
The investigation of family control in enterprises and gender diversity has emerged as a compelling area of study in several nations, such as Indonesia. This research study aims to understand how leverage and tangibility mediate between family control, gender diversity on profitability, and sales growth; using PLS-SEM tools, this quantitative investigation involved 942 companies listed on IDX from the 2019-2021 period for analysis. Sampling was carried out using a purposive sampling method. The results showed that leverage and tangibility could not significantly mediate between family control, female directors on profitability, and sales growth. These results have implications for owners, management, and directors in that supervisory board characteristics, such as heterogeneity and family control, can influence debt and asset policies and help improve company performance. The investigation of family control in enterprises and gender diversity has emerged as a compelling area of study in several nations, such as Indonesia. This research study aims to understand how leverage and tangibility mediate between family control, gender diversity on profitability, and sales growth; using PLS-SEM tools, this quantitative investigation involved 942 companies listed on IDX from the 2019-2021 period for analysis. Sampling was carried out using a purposive sampling method. The results showed that leverage and tangibility could not significantly mediate between family control, female directors on profitability, and sales growth. These results have implications for owners, management, and directors in that supervisory board characteristics, such as heterogeneity and family control, can influence debt and asset policies and help improve company performance.